Trochoidal X-ray Vector Radiography: Directional dark-field without grating stepping - Sharma, Y.; Bachche, S.; Kageyama, Masashi; Kuribayashi, M.; Pfeiffer, F.; Lasser, T.; Momose, Atsushi (Applied Physics Letters, 2018)
X-ray Vector Radiography (XVR) is an imaging technique that reveals the orientations of sub-pixel sized structures within a sample. Several dark-field radiographs are acquired by rotating the sample around the beam propagation direction and stepping one of the gratings to several positions for every pose of the sample in an X-ray grating interferometry setup. In this letter, we present a method of performing XVR of a continuously moving sample without the need of any grating motion. We reconstruct the orientations within a sample by analyzing the change in the background moire fringes caused by the sample moving and simultaneously rotating in plane (trochoidal trajectory) across the detector field-of-view. Avoiding the motion of gratings provides significant advantages in terms of stability and repeatability, while the continuous motion of the sample makes this kind of system adaptable for industrial applications such as the scanning of samples on a conveyor belt. Being the first step in the direction of utilizing advanced sample trajectories to replace grating motion, this work also lays the foundations for a full three dimensional reconstruction of scattering function without grating motion.
CRIS-Team Scopus Importer:2023-03-08